1995
DOI: 10.1111/j.1748-1716.1995.tb09976.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of exercise‐training on hypoxia and angiotensin II‐induced pulmonary vasoconstrictions

Abstract: The present study was undertaken to determine whether exercise-training for 6 weeks would inhibit pulmonary vasoconstriction induced by hypoxia in isolated, blood-perfused rat lungs. Hypoxic pulmonary vasoconstriction (HPV) and angiotensin II (AII)-induced pulmonary vasoconstriction were significantly less in the exercise-trained (ET) group than in the control (cont) group with all challenges. Normoxic pulmonary arterial and capillary pressures in the ET group were significantly lower than those in the cont gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

1997
1997
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 13 publications
1
16
0
Order By: Relevance
“…Alveolar hypoxia may potentially act by inducing increased in situ expression of vasoconstricting substances in the lung. In this connection, increased levels of catecholamines, vasopressin, angiotensin or ET-1 have been described during exercise [31][32][33]. However, their physiopathological significance in the exerciseinduced pulmonary haemodynamic and gas exchange abnormalities has not as yet been established.…”
Section: Discussionmentioning
confidence: 99%
“…Alveolar hypoxia may potentially act by inducing increased in situ expression of vasoconstricting substances in the lung. In this connection, increased levels of catecholamines, vasopressin, angiotensin or ET-1 have been described during exercise [31][32][33]. However, their physiopathological significance in the exerciseinduced pulmonary haemodynamic and gas exchange abnormalities has not as yet been established.…”
Section: Discussionmentioning
confidence: 99%
“…Rats were trained for 4 and 6 weeks under hypobaric hypoxia (equivalent to altitudes of 2500 and 5500 m). Kashimura et al 196 found that the increase in resting mean pulmonary arterial pressure with increasing equivalent altitude was lower in the 2 trained groups than in the control group and greater after 6 than after 4 weeks of exercise. 195 In a follow-up study, they showed that 6 weeks of training can attenuate the hypoxia-induced and angiotensin II-induced PH.…”
Section: Animal Experimentsmentioning
confidence: 99%
“…2000). Regarding the Ang II pathway, an exercise‐induced decrease in Ang II‐induced pulmonary vasoconstriction was present in rats that trained for 6 weeks (Kashimura et al . 1995).…”
mentioning
confidence: 99%